Runoff and Sediment Transport in the Arid Regions of Argentina and India - A Case Study in Comparative Hydrology - Sharma, K D; Meenti, M; Huvgen, J; Fernandez, P C; Vich, A (Annals of Arid Zone, 2016)
Comparative hydrology attempts to identify regions with similar environmental attributes and then compares the hydrological activities in these regions to facilitate the transfer of knowledge and exchange of techniques. As a case study, the arid zones of Argentina and India are compared. Runoff in both the regions is often generated by the Hortonian infiltration-excess overland flow, and runoff response to precipitation input tends to be rapid. The sediment transport is governed by the transport capacity of runoff rather than the availability. of erodible material to be transported. The magnitude of hydrological processes is different in response to the different rainfall regimes. This study identifies some of the strengths and weaknesses in our current knowledge of arid zone hydrology in both countries, and suggests that a more comprehensive treatment of the subject is likely to improve the prediction of the hydrological behaviour of such regions.